2021
DOI: 10.1186/s12889-021-12148-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of behavioural risk factors on communicable diseases: a systematic review of reviews

Abstract: Background The coronavirus (COVID-19) pandemic has highlighted that individuals with behavioural risk factors commonly associated with non-communicable diseases (NCDs), such as smoking, harmful alcohol use, obesity, and physical inactivity, are more likely to experience severe symptoms from COVID-19. These risk factors have been shown to increase the risk of NCDs, but less is known about their broader influence on communicable diseases. Taking a wide focus on a range of common communicable dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 104 publications
(153 reference statements)
0
9
0
1
Order By: Relevance
“…Obesity was identified to be a significant risk factor in this study, and obese pilgrims had a more than four-fold increased risk of RTIs. Review studies that explored the relationship between obesity and viral RTIs concluded that obesity raises the risk of contracting and having severe complications from ILI and COVID-19 [ 25 27 ]. Another study that investigated the correlation between the prevalence of obesity and COVID-19 infection rate in 54 countries detected that the residents of Saudi Arabia have the highest prevalence of obesity of 35% and it was significantly associated with the susceptibility to COVID-19 [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity was identified to be a significant risk factor in this study, and obese pilgrims had a more than four-fold increased risk of RTIs. Review studies that explored the relationship between obesity and viral RTIs concluded that obesity raises the risk of contracting and having severe complications from ILI and COVID-19 [ 25 27 ]. Another study that investigated the correlation between the prevalence of obesity and COVID-19 infection rate in 54 countries detected that the residents of Saudi Arabia have the highest prevalence of obesity of 35% and it was significantly associated with the susceptibility to COVID-19 [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, according to the rules of ‘Ihram’, scented toiletries including scented soaps, perfumes, or deodorant on pilgrim’s body or clothing are avoided. The religious and cultural preference of Muslims to avoid products that contain alcohol when alternatives are available may further explain the low compliance of using alcohol-based hand sanitiser among Hajj pilgrims [ 27 ]. Unlike the reported barrier in our 2019 Hajj study [ 7 ], the unavailability of soap and hand sanitisers was not a major hindrance for pilgrims who attended this Hajj to clean their hands, and this was possibly due to the distribution of a large volume of hygienic products at every Hajj sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity was identi ed to be a signi cant risk factor in this study, and obese pilgrims had a more than four-fold increased risk of RTIs. Review studies that explored the relationship between obesity and viral RTIs concluded that obesity raises the risk of contracting and having severe complications from ILI and COVID-19 [22][23][24]. Another study that investigated the correlation between the prevalence of obesity and COVID-19 infection rate in 54 countries detected that the residents of Saudi Arabia have the highest prevalence of obesity of 35% and it was signi cantly associated with the susceptibility to COVID-19 [25].…”
Section: Discussionmentioning
confidence: 99%
“…Although socioeconomic characteristics, lifestyle factors, poor metabolic health, and preexisting chronic conditions were suggested to be risk factors for COVID-19, the whole impactors are still elusive [4][5][6]. While vaccines, effective treatments, and mitigation measures have been launched to deal with COVID-19, understanding the risk factors of COVID-19 would be of great importance in building up people's health and preventing acute infectious disease in the future [7].…”
Section: Introductionmentioning
confidence: 99%